Generation of Corneal Epithelial Cells from Induced Pluripotent Stem Cells Derived from Human Dermal Fibroblast and Corneal Limbal Epithelium - Hayashi, Ryuhei (Public Library of Science, 2012)
Induced pluripotent stem (iPS) cells can be established from somatic cells. However, there is currently no established strategy to generate corneal epithelial cells from iPS cells. In this study, we investigated whether corneal epithelial cells could be differentiated from iPS cells. We tested 2 distinct sources: human adult dermal fibroblast (HDF)-derived iPS cells (253G1) and human adult corneal limbal epithelial cells (HLEC)-derived iPS cells (L1B41). We first established iPS cells from HLEC by introducing the Yamanaka 4 factors. Corneal epithelial cells were successfully induced from the iPS cells by the stromal cell-derived inducing activity (SDIA) differentiation method, as Pax6(+)/K12(+) corneal epithelial colonies were observed after prolonged differentiation culture (12 weeks or later) in both the L1B41 and 253G1 iPS cells following retinal pigment epithelial and lens cell induction. Interestingly, the corneal epithelial differentiation efficiency was higher in L1B41 than in 253G1. DNA methylation analysis revealed that a small proportion of differentially methylated regions still existed between L1B41 and 253G1 iPS cells even though no significant difference in methylation status was detected in the specific corneal epithelium-related genes such as K12, K3, and Pax6. The present study is the first to demonstrate a strategy for corneal epithelial cell differentiation from human iPS cells, and further suggests that the epigenomic status is associated with the propensity of iPS cells to differentiate into corneal epithelial cells.